A pineapple a day - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Could it be a fairy tale? Pineapples that are good for everybody, farmers, traders and consumers alike? Perhaps not. In 1999, around 170 Ghanaian pineapple growers organised themselves with the prime objective of getting a better price for their...